Creating English Environment Through “Queen of Language” Program - Uswatun Hasanah; Fayruzah El-Faradis; Sitti Khotijah (ELITE Association Indonesia, 2023)
ABSTRACT Creating english language environment is very important to all english learners. Because by this environment they could approved what they see and what they hear in their daily activities. Thus, english learning in ma'had Institut Dirosat Islamiyah Al-Amien (IDIA) conducted by teachers that create the environment learning in various program. One of it, is Queen of language to trigger their spirit and rehearse their skill in english learning. This research aims to know how is the creating of english environment through queen of language. By using qualitative, then describe that activity. Data collection by observation, interview. The result showed that the implementation of creating english language environment conducted in many ways. One of it is Queen of language program that consist of games and competitions. Competitions cope in 4 english language skills. The obstacles faced are the lack of english mastery, and the lack of their spirit in learning english. Keywords: Creating, English Environment, Queen of Language Program